Comparison of algorithms for automated femur fracture reduction. Issue 1 (24th September 2017) - Suero, Eduardo M.; Westphal, Ralf; Citak, Musa; Hawi, Nael; Liodakis, Emmanouil; Omar, Mohamed; Krettek, Christian; Stuebig, Timo
Abstract: Purpose: We designed an experiment to determine the comparative effectiveness of computer algorithms for performing automated long bone fracture reduction. Methods: Automated reduction of 10 3D fracture models was performed using two computer algorithms, random sample matching (RANSAM) and Z‐buffering (Z‐Buffer), and one of five options of post‐processing: none; iterative closest point algorithm (ICP); ICP‐X1; ICP‐X2; and ICP‐X3. We measured the final alignment between the two fragments for each algorithm and post‐processing option. Results: The RANSAM algorithm combined with postprocessing algorithm ICP‐X1 or ICP‐X3 resulted in the most accurate fracture reduction in the translational plane. No discernible difference was observed in the rotational plane. Automated reduction had more accurate translational displacement than telemanipulated manual reductions. Conclusion: This study supports the use of the RANSAM algorithm for automated fracture reduction procedures. The use of ICP algorithms provides further optimization of the initial reduction.